Antagonistic Interactions Between the cAMP-Dependent Protein Kinase and Tor Signaling Pathways Modulate Cell Growth in Saccharomyces cerevisiae - Ramachandran, Vidhya (Genetics Society of America, 2011)
Eukaryotic cells integrate information from multiple sources to respond appropriately to changes in the environment. Here, we examined the relationship between two signaling pathways in Saccharomyces cerevisiae that are essential for the coordination of cell growth with nutrient availability. These pathways involve the cAMP-dependent protein kinase (PKA) and Tor proteins, respectively. Although these pathways control a similar set of processes important for growth, it was not clear how their activities were integrated in vivo. The experiments here examined this coordination and, in particular, tested whether the PKA pathway was primarily a downstream effector of the TORC1 signaling complex. Using a number of reporters for the PKA pathway, we found that the inhibition of TORC1 did not result in diminished PKA signaling activity. To the contrary, decreased TORC1 signaling was generally associated with elevated levels of PKA activity. Similarly, TORC1 activity appeared to increase in response to lower levels of PKA signaling. Consistent with these observations, we found that diminished PKA signaling partially suppressed the growth defects associated with decreased TORC1 activity. In all, these data suggested that the PKA and TORC1 pathways were functioning in parallel to promote cell growth and that each pathway might restrain, either directly or indirectly, the activity of the other. The potential significance of this antagonism for the regulation of cell growth and overall fitness is discussed.